Characteristic of Bamboo Particleboard Bonded with Citric Acid - Ragil Widyorini; Ari Puspa Yudha; Yuditya Adifandi; Kenji Umemura; Shuichi Kawai (Wood Research Journal, 2013)
Converting biomass waste to high value-added product, such as biocomposite, tends to attract the interest of researcher and industry. Reducing the utilization of synthetic resin adhesives becomes one of the important points, considering the safe global environment. Binderlessboard is a product whose bonding depends mainly on the chemical composition of the raw materials. The aim of this research was to develop bio-based composites made from bamboo biomass waste materials. This report focused on the physical and mechanical properties of the particleboards. To improve the properties of the boards, the possibility of using citric acid was investigated and discussed. Petung bamboo particles (Dendrocalamus asper Backer) were used in this research. The contents of citric acid were ranged in 0% (binderlessboard), 10%, and 20% based on dried particles. The dimension of the boards was 25 x 25 x 0.7 cm, with the target density was 0.9 g/cm3. The particleboards were hot pressed at 200ºC and 220ºC for 10 and 15 min. The physical and mechanical properties of those particleboards were then evaluated based on Japanese Industrial Standard A 5908 for particleboard. The results showed that the physical and mechanical properties of the boards improved significantly by adding the citric acid. The bamboo particleboards obtained had good properties, with the spesific IB, specific MOR and specific MOE values under the optimum condition of 20 wt % citric acid content and 200ºC hot press were 0.44 MPa, 15.1 MPa and 4.6 GPa, respectively. It stated that bamboo particleboards bonded using citric acid had high performance on mechanical properties and good dimensional stability.